Contributions to a regional version of the category of welfare regime. A perspective based on the Argentine case: 'Welfare regimes' at the subnational level: overcoming methodological nationalism towards a regional and local translation - Paura, Vilma (2020)
The category of welfare regime has been applied in critical contributions to the study of protection schemes in Latin American countries. This article reviews early debates in which this category was employed in the European context, and the transition to its application by Latin American researchers to study the cases of their own countries. The manner in which the perspective of welfare regimes and related conceptual tools were adapted to propose regional and local analyses of Latin America is also discussed. Starting with an analysis of how the Argentine case was understood, the approaches that characterized the regimes of the region as hybrid, incomplete, or embryonic are then analyzed and some possible vectors for a critical update are proposed. The theoretical review takes into account the considerable existing bibliography on Latin American welfare regimes.